Chemical microenvironments within macroalgal assemblages: Implications for the inhibition of kelp recruitment by turf algae. (13th February 2019) - Layton, Cayne; Cameron, Matthew J.; Shelamoff, Victor; Fernández, Pamela A.; Britton, Damon; Hurd, Catriona L.; Wright, Jeffrey T.; Johnson, Craig R.
Abstract: Kelp forests around the world are under increasing pressure from anthropogenic stressors. A widespread consequence is that in many places, complex and highly productive kelp habitats have been replaced by structurally simple and less productive turf algae habitats. Turf algae habitats resist re‐establishment of kelp via recruitment inhibition; however, little is known about the specific mechanisms involved. One potential factor is the chemical environment within the turf algae and into which kelp propagules settle and develop. Using laboratory trials, we illustrate that the chemical microenvironment (O2 concentration and pH) 0.0–50 mm above the substratum within four multispecies macroalgal assemblages (including a turf‐sediment assemblage and an Ecklonia radiata kelp‐dominated assemblage) are characterized by elevated O2 and pH relative to the surrounding seawater. Notably however, O2 and pH were significantly higher within turf‐sediment assemblages than in kelp‐dominated assemblages, and at levels that have previously been demonstrated to impair the photosynthetic or physiological capacity of kelp propagules. Field observations of the experimental assemblages confirmed that recruitment of kelp was significantly lower into treatments with dense turf algae than in the kelp‐dominated assemblages. We demonstrate differences between the chemical microenvironments of kelp and turf algae assemblages that correlate with differences in kelp recruitment, highlighting how degradation of kelp habitats might result in the persistence of turf algae habitats and the localized absence of kelp.